Has Increased Rollout of Direct Acting Antiviral Therapy Decreased the Burden of Late Presentation and Advanced Liver Disease in Patients Starting Hepatitis C Virus Therapy in Germany?. Issue 2 (February 2020) - Bischoff, Jenny; Boesecke, Christoph; Ingiliz, Patrick; Berger, Florian; Simon, Karl-Georg; Lutz, Thomas; Schewe, Carl K.; Schulze zur Wiesch, Julian; Hueppe, Dietrich; Christensen, Stefan; Mauss, Stefan; Baumgarten, Axel; et al.
Abstract : Goals and Background: International guidelines recommend prioritized treatment initiation in hepatitis C virus (HCV)-infected patients with advanced liver disease. We aimed to evaluate whether the widespread usage of direct acting antivirals (DAAs) has led to a decrease in late presentation for care. Study: Data derived from the multicenter German Hepatitis C Cohort (GECCO) was analyzed. Treatment naive HCV-infected patients initiating DAA-based treatment between January 2014 and September 2017 were included. Advanced liver disease was defined by aspartate aminotransferase to platelet ratio index score ≥1.5, METAVIR≥F3, or FibroScan ≥9.5 kPa. Period prevalence and risk factors for late presentation were evaluated. Results: Six hundred fifty-three HCV-monoinfected and 210 HIV/HCV-coinfected patients (mean age, 48.6±12.7 y; 65.5% male) were included. Overall 32.5% of patients had advanced liver disease. In 2014 39.4% of patients presented with advanced liver disease, decreasing to 30.1%, 34.4%, and 26.4% in the years 2015, 2016, and 2017 ( P =0.057), respectively. Patients with and without advanced liver disease differed in age ( P <0.0001), CD4 + ⩽350/µL ( P =0.027), genotype ( P =0.005), transmission route ( P =0.047), body mass index ( P <0.001), and time since diagnosis ( P =0.007). In the multivariable binary logistic regression analysis GT3, age above 45 years and being diagnosed >2 years ago were positively and HCV transmission through men who have sex with men was negatively associated with advanced liver disease. Conclusions: Overall 32.5% of patients presented with advanced liver disease. We observed a trend toward a lower proportion of patients starting treatment late. GT3, age, years since HCV diagnosis and HCV transmission route were identified as risk factors for presentation with advanced liver disease. Abstract : Supplemental Digital Content is available in the text.